Synergizing Halal and Sustainable Tourism Practices: Their Influence on Tourist Satisfaction - Maulida, Annisaturrahmah; Munandar, Jono Mintarto; Sumertajaya, I Made; Jasiulewicz, Anna (Universitas Brawijaya, Indonesia, 2025)
As a sector anticipated to prosper in the long run, the Indonesian tourism industry should create a sustainable tourism model that takes into account the social, environmental, and economic impacts both now and in the future, while addressing the needs of local communities, the environment, the industry, and visitors. Considering that Indonesia is a country with a majority Muslim population, implementing halal tourism is very important for Muslim tourists in Indonesia. Halal tourism is a concept that focuses on meeting the essential needs of Muslims at tourist destinations, including provisions for worship, purification, and travel in accordance with Sharia law. This study aims to examine the impact of sustainable and halal tourism on tourist satisfaction within the Mandalika Special Economic Zone. This study was conducted among 200 Muslim tourists who visited the Mandalika Special Economic Zone by administering an online questionnaire via Google Forms. The collected data were analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling), which revealed that sustainable tourism significantly impacts halal tourism. In turn, halal tourism significantly affects tourists' perceived value, which in turn significantly influences tourist satisfaction. Therefore, to achieve or increase tourist satisfaction, it is necessary to increase sustainable tourism, halal tourism, and tourist perceived value.